PENERAPAN STRATEGI PEMBELAJARAN ACTIVE KNOWLEDGE SHARING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA KELAS V MIN 1 SABANG - Daniah; Rina Febiyanti; Azhar (Published by Center for Research and Community Service (LP2M) in cooperation with the Postgraduate Program of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2023)
The lack of critical thinking skills of students in schools greatly influences student learning outcomes. Judging from the learning process of class V MIN 1 Sabang students, there is a problem, namely when students are asked a question, the student can provide an answer but cannot explain the reasons or opinions related to the answer. The teacher has used learning strategies but has not been able to develop students' critical thinking skills during the learning process. One strategy that can be implemented is the active knowledge sharing strategy. The aims of this research are (1) to find out the activities of teachers and students after using active knowledge sharing strategies in class V/b (2) to find out critical thinking skills and student learning outcomes using active knowledge sharing strategies in class V/b. This research took the form of Classroom Action Research (PTK), carried out in 4 stages, namely planning, implementation, observation and reflection. The instruments of this research are teacher activity sheets, student activities, critical thinking test questions and learning outcomes. The results of the research show that: (1) teacher activity using active knowledge sharing strategies in cycle I was 76.56% in the good category and increased in cycle II to 92.18% in the very good category, (2) research results of student activity using active knowledge strategy in cycle I was 73.43% in the good category and in cycle II it was 93.75% in the very good category, (3) the critical thinking ability test in cycle I in cycle I was at 61.2% categorized as quite critical and cycle II experienced an increase of 82.4% categorized as very critical, (4) cycle I student learning outcomes were 44% in the poor category and cycle II experienced an increase in student learning outcomes of 84% in the very good category.